2013
DOI: 10.1097/mcp.0b013e328365ab89
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for complex behavioral insomnia in children with neurodevelopmental disorders

Abstract: Children and adolescents with neurological disorders frequently have complex sleep disorders that require treatment. Understanding the basic pathology and treatment strategies provides an opportunity to improve well being and quality of life in those affected by NDD and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 69 publications
0
55
0
2
Order By: Relevance
“…temperament, age), parental, and environmental factors and on the underlying disease. Clearly, the involvement of parents as agents for changing problematic sleep behaviors is fundamental; cognitive‐behavioral techniques involving parents have been shown to be effective in improving significantly quality of life and well‐being of patients and caregivers (Grigg‐Damberger & Ralls, ; Jan et al., ). Training group of parents in behavioral approaches to manage sleep problems represents a novel behavioral approach: Stuttard et al.…”
Section: Treatment Of Chronic Insomnia In Neurodevelopmental Disabilimentioning
confidence: 99%
See 1 more Smart Citation
“…temperament, age), parental, and environmental factors and on the underlying disease. Clearly, the involvement of parents as agents for changing problematic sleep behaviors is fundamental; cognitive‐behavioral techniques involving parents have been shown to be effective in improving significantly quality of life and well‐being of patients and caregivers (Grigg‐Damberger & Ralls, ; Jan et al., ). Training group of parents in behavioral approaches to manage sleep problems represents a novel behavioral approach: Stuttard et al.…”
Section: Treatment Of Chronic Insomnia In Neurodevelopmental Disabilimentioning
confidence: 99%
“…Clearly, the involvement of parents as agents for changing problematic sleep behaviors is fundamental; cognitive-behavioral techniques involving parents have been shown to be effective in improving significantly quality of life and well-being of patients and caregivers (Grigg-Damberger & Ralls, 2013;Jan et al, 2008). Training group of parents in behavioral approaches to manage sleep problems represents a novel behavioral approach: Stuttard et al (Stuttard, Beresford, Clarke, Beecham, & Curtis, 2015) reported the findings from a preliminary evaluation of a group-delivered intervention routinely delivered by a Child and Adolescent Mental Health Service Learning Disability team in England: parents (n = 23) of children with intellectual disabilities were recruited and the follow-up was of 6 months.…”
Section: Nonpharmacological Treatmentmentioning
confidence: 99%
“…(4)) Among children with neurodevelopmental disorders, prevalence is even higher, up to 80%. (5, 6) BSPs impede development of executive function,(7) and may increase later need for special education. However, healthy sleep practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…obstructive sleep apnoea, periodic limb movements) should be identified and referral considered where necessary 10,11…”
Section: Assessment Of Sleep Disordersmentioning
confidence: 99%
“…Sleep problems such as reduced total sleep duration (TSD), longer SOL, nocturnal awakenings (which may last 2–3 hours) and early morning awakenings are common in children with autism spectrum disorder, with prevalences reported between 30–86% 9,11,24. Children with autism spectrum disorder often have abnormal melatonin levels (especially at night) and an abnormal circadian rhythm, and some have genetic abnormalities in melatonin production or melatonin receptor function 9,24.…”
Section: About Melatoninmentioning
confidence: 99%